A comprehensive public open space categorization using classification system for sustainable development of public open spaces - Nochian, Ashkan; Mohd Tahir, Osman; Maulan, Suhardi; Rakhshandehroo, Mehdi (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Our quality of life significantly depends on open spaces. They offer facility provision for a wide range of social interactions and provide habitats for flora and fauna. A classification of spaces would be useful in preparing public open space policies and fulfilling structure plan. This study aims to propose a comprehensive open space categorization using classification system for Malaysia. A deep investigation in sources in Malaysia reveals that there is lack of comprehensive classification of open spaces and just a hierarchy of open spaces presented. A critical literature review were carried out for this study to understand the approaches of this comprehensive classification and adapted them according to Malaysia context. In order to come up with a comprehensive classification in Malaysia, an analysis of comparison between several cities in different countries was done. The outcomes of the study will provide a systematic classification use for planner and policy makers in preparing open space strategies and in setting development plan policies. It is also useful for designers to obtain the best possible conceptual ideas when designing open spaces.